EFEKTIFITAS PENERAPAN KURIKULUM PADA MATA KULIAH HUKUM PIDANA ISLAM (STUDI KASUS PRODI JINAYAH) - Ramadani Ramadani; Zaid Alfauza Marpaung; Aidil Putra Dalimunthe (Smart Education, 2025)
Abstract: The curriculum is agreed upon as the method and path taken in the process of achieving goals. In Indonesia, there has been a process of curriculum revision starting from the 1947 syllabus, the 1994 syllabus, the 2006 syllabus, the 2013 syllabus, and uniquely, the curriculum currently in use. The main task of jinayah law is to make the perpetrator aware not to repeat similar actions, which then leads to a disciplined attitude that creates a positive impression on others, so as not to fall into sin. committing criminal acts, as well as individuals who have committed those criminal acts, and if you have not been caught, you will think long and hard about repeating your activities. Thus, peace will be created in this world. The obligation to understand Jinayah material is urgent, because the status of the University is an Islamic educational institution and the concentration in the study program also leads to Islamic Criminal Law itself. Therefore, it is very inappropriate if students of the Islamic Criminal Law program do not understand the essence of the study program they are undertaking. In fact, this contradicts the CPL (Curriculum Learning Plan) of the Islamic Criminal Law (Jinayah) program, because the students do not fully master the study of Jinayah in its broad or narrow sense. Therefore, the researcher intends to explicitly examine the curriculum of the Islamic Criminal Law (Jinayah) program in relation to Jinayah itself. Keyword : curriculum, courses, Islamic criminal law. Abstrak: Kurikulum disepakatai menjadi metode dan jalur yang diambil dalam proses pencapaian tujuan. Di Indonesia, telah terjadi proses rekap kurikulum mulai dari silabus 1947, silabus 1994, silabus 2006, silabus 2013 dan uniknya kurikulum yang digunakan saat ini. Tugas utama hukum jinayah yaitu memberikan kesadaran pelakunya untuk tidak kembali berbuat hal serupa kemudian bermuara pada sikap disiplin tersebut menciptakan kesan positif bagi orang lain, agar tidak terjerumus ke dalam dosa. melakukan tindakan kriminal, serta individu yang telah melakukan tindakan kriminal tersebut dan Jika Anda belum tertangkap, Anda akan berpikir panjang dan sulit untuk mengulangi aktivitas Anda. Dengan demikian, perdamaian akan tercipta di dunia ini. Kewajiban memahami materi Jinayah adalah hal yang urgent, dikarenakan status Universitas adalah sebuah lembaga pendidikan Islam dan konsentrasi pada program studi juga menjurus kepada Hukum Pidana Islam itu sendir, jadi sangatlah tidak ajar jika mahasisa prodi Hukum Pidana Islam tidak memahami hakikat dari program studi yang sedang diampu mereka. Bahkan hal ini berseberanagn dengan CPL kuriulum hukum pidana islam (jinayah), dikarenakan para mahasiswa tidak begitu menguasai kajian jinayah yang sebenarnya dalam arti luas maupun dalam arti sempit. Untuk itu peneliti hendak mengkaji secara eksplisit terhadap kurikulum pada program studi hukum pidana islam (jinayah) pada jinayah itu sendiri. Kata kunci : kurikulum, mata kuliah, hukum pidana islam.